Causal Ambiguity, Barriers to Imitation, and Sustainable Competitive Advantage - Reed, Richard; DeFillippi, Robert (Academy of Management Review, 1990)
This article addresses the issues of competitive advantage and competitor imitation. It is argued that tacitness, complexity, and specificity in a firm's skills and resources can generate causal ambiguity in competency-based advantage, and thus raise barriers to imitation. Reinvestment in causally ambiguous competencies is necessary to protect the advantage. Without reinvestment, attritional effects of continued competitive action will cause decay in the barriers to imitation. From this theorizing, research propositions are suggested, which, ultimately, will lead to an improved understanding of competitive advantage sustainability.